New Trends on Genome and Transcriptome Characterizations - Vincenzo Manca; Rosalba Giugno (Frontiers Media SA, 2021)
This Research Topic is devoted to bioinformaticians, geneticists and researchers who study or apply methods and algorithms for genomes and transcriptome analyses, aimed at understanding pathology discriminations and classifications. Papers are encouraged that use unconventional approaches and/or where mathematical and computational concepts are applied to biological and medical contexts in original ways. The contributions presented in the Topic should be of interest also to a wide class of scientists and students involved in the several fields where genomic and transcriptomic approaches are becoming essential for future investigations.